Pengaruh Kunyit (Curcuma Longa) Sebagai Galagtagog Alami Terhadap Peningkatan Produksi Air Susu Ibu (ASI): Tinjauan Literatur - Lingga Puspita Sari; Lathifah Arub; Aururah Fitri Imaniza (Jurnal Medicare, 2025)
Optimal breast milk production is key to meeting the nutritional needs of infants. However, many breastfeeding mothers still experience obstacles in breast milk production. One of the commonly used traditional interventions is turmeric (Curcuma longa), an herbal plant containing curcumin and has long been used as a natural galactagogue. The purpose of this study was to systematically review the scientific literature on the effect of turmeric on breast milk production. The results of the study indicate that giving turmeric in various forms (extracts, herbal medicines, supplements) has the potential to increase breast milk production through hormonal mechanisms and anti-inflammatory effects. However, further research is still needed with stronger experimental methods to support its use in clinical practice.